Addition of Hyperbaric Oxygen Therapy vs Standard Therapy in SSNHL - Komang Adi Praja Semara Putra (Rifa'Institute, 2022)
The background of sudden sensorineural hearing loss is that occurs suddenly, with unknown causes, and the number of cases increases with age. The modality of therapy that is often used today is empiric therapy. The purpose of this literature review is to determine the impact of adding hyperbaric oxygen therapy compared to standard therapy in cases of sudden sensorineural hearing loss. Methods The article search was carried out in various valid online data centers, namely PubMed, Science Direct, Cochrane Library, and Google Scholar. Looking for articles that discuss the addition of hyperbaric oxygen therapy in sudden sensorineural hearing loss. The results search yielded 1 observational study and 2 systematic studies. The addition of hyperbaric oxygen therapy provides a better clinical outcome. Conclusion: Hyperbaric oxygen therapy has a better effect than standard therapy only in cases of sudden sensorineural hearing loss.